An age‐related numerical and functional deficit in CD19+CD24hiCD38hi B cells is associated with an increase in systemic autoimmunity. Issue 5 (19th July 2013) - Duggal, Niharika A.; Upton, Jane; Phillips, Anna C.; Sapey, Elizabeth; Lord, Janet M.
Summary: Autoimmunity increases with aging indicative of reduced immune tolerance, but the mechanisms involved are poorly defined. In recent years, subsets of B cells with immunoregulatory properties have been identified in murine models of autoimmune disorders, and these cells downregulate immune responses via secretion of IL10. In humans, immature transitional B cells with a CD19 + CD24 hi CD38 hi phenotype have been reported to regulate immune responses via IL10 production. We found the frequency and numbers of CD19 + CD24 hi CD38 hi cells were reduced in the PBMC pool with age. IL10 expression and secretion following activation via either CD40, or Toll‐like receptors was also impaired in CD19 + CD24 hi CD38 hi B cells from healthy older donors. When investigating the mechanisms involved, we found that CD19 + CD24 hi CD38 hi B‐cell function was compromised by age‐related effects on both T cells and B cells: specifically, CD40 ligand expression was lower in CD4 T cells from older donors following CD3 stimulation, and signalling through CD40 was impaired in CD19 + CD24 hi CD38 hi B cells from elders as evidenced by reduced phosphorylation (Y705) and activation of STAT3. However, there was no age‐associated change in expression of costimulatory molecules CD80 and CD86 on CD19 + CD24 hi CD38 hi cells, suggesting IL10‐dependent immune suppression is impaired, but contact‐dependent suppressive capacity is intact with age. Finally, we found a negative correlation between CD19 + CD24 hi CD38 hi B‐cell IL10 production and autoantibody (Rheumatoid factor) levels in older adults. We therefore propose that an age‐related decline in CD19 + CD24 hi CD38 hi B cell number and function may contribute towards the increased autoimmunity and reduced immune tolerance seen with aging.